HUBUNGAN KONFORMITAS TEMAN SEBAYA DENGAN BULLYING PADA SISWA LAKI-LAKI DI SEKOLAH SMA NEGERI 4 SINGARAJA - sanistia hana nandisa; Prof. Dr Kadek Suranata,S.Pd.,M.Pd.,Kons (Indonesian Counselor Association (IKI), 2023)
Bullying continues to increase every year. High number of cases Bullying at school is very worrying. Where the victims of bullying will be have deep trauma. One of the factors that causes this to happen Bullying is due to conformity from peers. Form conformity peers who can give rise to bullying behavior are forms negative conformity. Peers become important to individuals because Individuals as teenagers want to belong and be accepted as part of something groups, so that teenagers or individuals tend to change their behavior according to the wishes of the group he joins and spends more of his time with peers rather than with family. This research is quantitative research that uses as many research subjects as possible 150 students. In this research, the aim is to look for relationships Peer conformity and bullying behavior. The sampling technique Simple random sampling was used because the research subjects were homogeneous, namely using male students. Research result shows that there is a significant and positive relationship between peer conformity and bullying, with a correlation value of 0.710. This means that the higher the peer conformity, the higher bullying behavior in male students. From the results of the determination test, the amount obtained was 0.505 or 50.5%, which means the peer conformity variable (X) provides contribution of 50.5% to the bullying variable (Y). While the remaining 49.5% influenced by other variables outside the research.